The impact of acting training on emotion recognition and expression: a systematic review - Chu, Vivian Ching-Mei; Chin, Ya-Wen; Chou, Margot Meng-Cheng; Lavi, Iris; Seaton, Maisie; Labidi, Eya; Ong, Jing Yi; Feaver, Isabelle; Wu, Alison Fang-Wei (Frontiers in Psychology, 2026)
IntroductionActing training focuses on improving actors’ emotion recognition and expression, and it has been used to strengthen individuals’ emotional skills in both artistic and non-artistic contexts. However, when examining the impact of this training on emotion recognition and expression in studies outside the arts, diverse research designs resulted in inconsistent findings or limitations for comparison across studies.MethodWe reviewed and evaluated the research design and evidence.ResultsThe 32 included articles show that acting-based interventions have been employed across diverse areas, including clinical, occupational and educational contexts, and these interventions could improve emotion recognition and expression. We examine the possible reasons for the inconsistency found in the literature, evaluating assessment tools and training content.DiscussionWe suggest addressing the underlying mechanism of the acting-based intervention’s impact on emotion recognition and expression skills and subsequently propose future research directions.Systematic review RegistrationDoi: https://doi.org/10.17605/OSF.IO/R2KTB.